An organisational approach to engineer emergence within holarchies. (22nd November 2010) - Cossentino, Massimo; Galland, Stephane; Gaud, Nicolas; Hilaire, Vincent; , Abderrafiaa Koukam
An open issue in self-organisation is how to engineer emergent behaviours. This issue is also of interest for engineering holonic multi-agent systems as any level of a holarchy is dependant of the emergent behaviours of its sub-levels. In order to tackle this specific feature of holonic multi-agent systems, the capacity concept which abstracts a know-how from its concrete realisation is introduced. The use of this concept is illustrated in this paper through a case study using the ASPECS development process which enables the analysis, design, implementation and deployment of holonic multi-agent systems and integrates the capacity as a core concept of it is underlying metamodel, called capacity-role-interaction-organisation (i.e., CRIO).